Crystal cell rupture after injury in Drosophila requires the JNK pathway, small GTPases and the TNF homolog Eiger. - Bidla, G.; Dushay, M.S.; Theopold, U. (Journal of Cell Science, 2007)
The prophenoloxidase-activating cascade is a key component of arthropod immunity. Drosophila prophenoloxidase is stored in crystal cells, a specialized class of blood cells from which it is released through cell rupture. Within minutes after bleeding, prophenoloxidase is activated leading to visible melanization of the clot matrix. Using crystal cell rupture and melanization as readouts to screen mutants in signal transduction pathways, we show that prophenoloxidase release requires Jun N-terminal kinase, small Rho GTPases and Eiger, the Drosophila homolog of tumor necrosis factor. We also provide evidence that in addition to microbial products, endogenous signals from dying hemocytes contribute to triggering and/or assembly of the prophenoloxidase-activating cascade, and that this process can be inhibited in vitro and in vivo using the viral apoptotic inhibitor p35. Our results provide a more comprehensive view of immune signal transduction pathways, with implications for immune reactions where cell death is used as a terminal mode of cell activation.